DOBROSTAN PRACOWNIKÓW A ZARZĄDZANIE WSPÓŁCZESNYMI ORGANIZACJAMI - Strykowska, Maria (Wydział Prawa i Administracji UAM, 2009)
The paper aims to demonstrate the convergence of interests of representatives of two research fields: management sciences and psychology. First, humanistic psychology and, more recently, positive psychology, have dealt with the self-actualisation of individuals and their well-being. For an adult, the most important sphere of self-actualisation is work. Self-actualisation in an organisation is possible owing to the application of participatory management concepts based on empowering employees, which consequently contributes to better performance and efficiency. It appears, however, that empowering employees does not always lead to better well-being. This is demonstrated using the Hackman and Oldham motivation model, from which it follows that management styles should be suited to individual types.
EMPLOYEE WELL-BEING AND MANAGEMENT OF CONTEMPORARY ORGANISATIONS